OPTIMALISASI KELAS IBU HAMIL MENGGUNAKAN APLIKASI GEMBIL MENUJU IBU HAMIL SEHAT - Lisnawati; Widiyanti, Rani; Atmaja, Surya (Edukasi Masyarakat Sehat Sejahtera (EMaSS) : Jurnal Pengabdian kepada Masyarakat, 2024)
Sunyaragi is one of the community health centers that has quite a large number of pregnant women and already has classes for pregnant women, but they are not yet running regularly. Community Health Center also has not utilized virtual classes for pregnant women, even though all pregnant women have joined the WhatsApp group. The GEMBIL application (pregnant mother game) is an interesting, fun and educational information technology media innovation that can be used as media in pregnant mother classes. The GEMBIL application consists of 3 parts. GEMBIL 1 contains about pregnancy, GEMBIL 2 contains about childbirth and postpartum and GEMBIL 3 contains about newborn babies. This application was created in collaboration with IT (information and technology) experts in 2022. This community service activity is a follow-up to research activities carried out in 2022. The aim is to increase pregnant women's knowledge about care during pregnancy, childbirth and postpartum. The method used is through online classes for pregnant women using the GEMBIL application, held in 3 meetings with a total of 10 pregnant women. Evaluation was carried out using pretest and posttest questionnaires. The results of the analysis using the dependent T test show a p value of 0.00, meaning that the use of the GEMBIL application has an effect on increasing pregnant women's knowledge about pregnancy, childbirth, postpartum and newborn care. This application is effectively used as an alternative for holding virtual classes for pregnant women.